PENGARUH TERPAAN IKLAN JUDI ONLINE DAN INTENSITAS KOMUNIKASI DENGAN TEMAN SEBAYA TERHADAP MINAT BERMAIN JUDI ONLINE - Hidayat, Wahyu; Setyabudi, Djoko; Surayya Ulfa, Nurist (Interaksi Online, 2024)
Online gambling transactions in Indonesia have increased significantly, despite the fact that such activities are prohibited by Indonesian law. Surveys indicate that the majority of the population is aware of the presence of online gambling advertisements spread across the internet and social media, and many have friends who are involved in online gambling. These findings suggest that despite the legal ban on gambling, various social and technological factors encourage people to remain engaged in such activities. This study aims to examine the influence of exposure to online gambling advertisements and the intensity of communication with peers on the interest in online gambling. The research adopts a quantitative explanatory approach, based on assumptions from cognitive response theory and social learning theory, using non-probability sampling techniques with purposive sampling methods. Data was collected using a questionnaire distributed to 100 respondents, consisting of males and females aged 18–43 years, residing in Central Java, who have seen online gambling advertisements and have acquaintances or friends who engage in online gambling. The results show that exposure to online gambling advertisements has a negative influence on the interest in online gambling, while the intensity of peer communication has a positive influence on the interest. Based on these findings, it can be concluded that exposure to online gambling advertisements and the intensity of communication with peers are two significant factors influencing interest in online gambling.